2010
DOI: 10.1136/jnnp.2009.196253
|View full text |Cite
|
Sign up to set email alerts
|

EEG correlated functional MRI and postoperative outcome in focal epilepsy

Abstract: Thornton 2 AbstractBackground: The main challenge in assessing patients with epilepsy for resective surgery is localising seizure onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 37 publications
10
134
1
3
Order By: Relevance
“…2 Recent studies of the use of simultaneous EEG/fMRI during the seizure-free period have reported concordance between interictal hemodynamic responses (ie, the irritative zone) and ictal electroclinical data. [3][4][5][6][7] These findings corroborate previous EEG studies showing strong correlation between the zone of earliest (interictal) spike and the SOZ, indicating a common epileptogenic brain area. 8 The irritative zone may thus encompass the SOZ.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…2 Recent studies of the use of simultaneous EEG/fMRI during the seizure-free period have reported concordance between interictal hemodynamic responses (ie, the irritative zone) and ictal electroclinical data. [3][4][5][6][7] These findings corroborate previous EEG studies showing strong correlation between the zone of earliest (interictal) spike and the SOZ, indicating a common epileptogenic brain area. 8 The irritative zone may thus encompass the SOZ.…”
supporting
confidence: 81%
“…The FWE criterion resulted in extensive and multifocal clusters (mean, 111 cm 3 ; range, 9 -198 cm 3 ; mean number of clusters, 37; range, 6 -50). BOLD signal correlates were present in the resected area in 3 of 4 patients and in the SOZ (defined electroclinically) in 4 of 6 patients.…”
Section: Family-wise Errormentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the study, proportions of patients who display IED-related changes in the BOLD signal ranged from 67% to 83% (Kobayashi et al, 2006;Salek-Haddadi et al, 2006). The most clinically useful BOLD changes are activations, since identification of a single activation cluster was found to be concordant with electro-clinical symptoms in over 80% of cases (Krakow, 1999;Salek-Haddadi et al, 2006;Thornton et al, 2010) and are good predictors of positive surgical outcome . Importantly, a number of studies showed that EEG-fMRI has the potential to reveal the components of ENs.…”
Section: Combined Eeg and Fmrimentioning
confidence: 94%
“…The localization of the origin of interictal epileptiform discharges (IEDs) plays a major role in the presurgical work-up of patients with focal refractory epilepsy, especially, using MEG (Englot et al, 2015;Knowlton, 2008;Ossenblok et al, 2007;Pataraia et al, 2004;Stefan et al, 2003) and more recently simultaneous EEG and fMRI (Thornton et al, 2010;Zijlmans et al, 2002). Nowadays the identification of the network underlying the IEDs is an auxiliary tool for the question where to place an intracortical grid or stereotactic depth electrodes for presurgical evaluation in refractory candidates (Pataraia et al, 2004;Schulz et al, 2000;van Houdt et al, 2013van Houdt et al, , 2012Walczak et al, 1990).…”
Section: Introductionmentioning
confidence: 99%